PUSAT PERAWATAN DEPRESI REMAJA DI BANJARBARU YOUTH TREATMENT CENTER BANJARBARU - Sukma, Ditha Tiara; Muchamad, Bani Noor (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
Depression is a medical condition that negatively impacts a person’s thoughts, actions, feelings, and mental health. Depressed individuals tend to feel trapped in a hopeless condition, no help, full of rejection, feeling worthless, which encourages the sufferer to commit suicide. According to data from The Ministry of Health shows that the prevalence of mental emotional disorders in people aged over 15 years in South Kalimantan has increased. In addition, South Kalimantan only has facilities for people with severe mental illness, there are no special facilities to treat people with mental disorders especially depression. There are many young people who have depression however, not much of them asking for professional help because of stigma among society and a lack of understanding, preventing people with depression from getting proper help. Design of Youth Treatment Center applied method gestalt psychology and space perception concept. This design is to provide a treatment for depression adolescents that can change stigma and increase public awareness of mental health.